2016
DOI: 10.1111/j.1755-3768.2016.0601
|View full text |Cite
|
Sign up to set email alerts
|

Retinal function and morphology in Mitf mutant mice

Abstract: PurposeThe Mitf (microphthalmia‐associated transcription factor) gene that is essential for the normal development of the retinal pigment epithelium (RPE). Mutations in this gene can cause hypopigmentation, microphthalmia and blindness. The purpose of this work was to analyze the retinal function and morphology in mice with specific Mitf mutations.MethodsThe following Mitf mutations were used: Mitfmi‐enu122 (398), Mitfmi‐wh/+, Mitfmi‐wh/Mitfmi and wild type (C5BL/6J) mice as a control. Mice were anesthetized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results of a microarray analysis in the C57BL/6j mice (RRID:MGI:5657312) showed that the expression of this gene is higher in the rod photoreceptors in P4 than that in other parts of the retina, and it is likely that ADCY6 is the specific gene of retinal photoreceptors in the mouse (Postel, Bellmann, Splith, & Ader, ). MITF is another member of the microphthalmia family of transcription factors (MiT) that is expressed in the retina (Garcia Llorca, Gudmundsdóttir Aspelund, Ogmundsdóttir, Steingrimsson, & Eysteinsson, ) and also directly targeted by the miR‐182 and miR‐96. A study on mice using target site assays showed that MITF was a direct target of miR‐182 and miR‐96 (Weston et al, ).…”
Section: Further Hypotheses On the Role Of The Mir‐183 Cluster In Thementioning
confidence: 99%
“…The results of a microarray analysis in the C57BL/6j mice (RRID:MGI:5657312) showed that the expression of this gene is higher in the rod photoreceptors in P4 than that in other parts of the retina, and it is likely that ADCY6 is the specific gene of retinal photoreceptors in the mouse (Postel, Bellmann, Splith, & Ader, ). MITF is another member of the microphthalmia family of transcription factors (MiT) that is expressed in the retina (Garcia Llorca, Gudmundsdóttir Aspelund, Ogmundsdóttir, Steingrimsson, & Eysteinsson, ) and also directly targeted by the miR‐182 and miR‐96. A study on mice using target site assays showed that MITF was a direct target of miR‐182 and miR‐96 (Weston et al, ).…”
Section: Further Hypotheses On the Role Of The Mir‐183 Cluster In Thementioning
confidence: 99%